America and the law of nations, 1776-1939 - Janis, Mark W. (Oxford : Oxford University Press, 2010)
This book narrates the important role that international law has played in America & the crucial if complex story of America's place in promoting & frustrating international law. Based on the stories of key figures in American history & written in an accessible style, it is a must read for anyone interested in America's place in the world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International law -- United States